GRADE Equity Guidelines 2: Considering health equity in GRADE guideline development: Equity extension of the Guideline Development Checklist - Akl E. (2017)
© 2017 Elsevier Inc. Objective: To provide guidance for guideline developers on how to consider health equity at key stages of the guideline development process. Study Design and Setting: Literature review followed by group discussions and consensus building. Results: The key stages at which guideline developers could consider equity include setting priorities, guideline group membership, identifying the target audience(s), generating the guideline questions, considering the importance of outcomes and interventions, deciding what evidence to include and searching for evidence, summarizing the evidence and considering additional information, wording of recommendations, and evaluation and use. We provide examples of how guidelines have actually considered equity at each of these stages. Conclusion: Guideline projects should consider the aforementioned suggestions for recommendations that are equity sensitive.